2008
DOI: 10.1161/atvbaha.108.162305
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of the CXC Chemokine GROα in Atherosclerosis and Plaque Destabilization

Abstract: Objective-We examined the role of the CXCR2 ligand growth-related oncogene (GRO) ␣ in human atherosclerosis. Methods and Results-GRO␣ levels were examined by enzyme immunoassay, real-time quantitative RT-PCR, and cDNA microarrays. The in vitro effect of statins on GRO␣ was examined in endothelial cells and THP-1 macrophages. Our main findings were: (1) GRO␣ was among the 10 most differentially expressed transcripts comparing peripheral blood mononuclear cells (PBMCs) from patients with coronary artery disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…Previous studies have shown that GRO␣ can support monocyte arrest to the endothelium in models of inflammation and may thereby be relevant for the development of atherosclerosis (45). Moreover, enhanced plasma levels of GRO␣ in patients with coronary artery disease have been demonstrated (46). Although these measurements were based on GRO␣ expression in peripheral monocytes, it is tempting to speculate that activated endothelial cells could contribute significantly to the total expression and secretion of GRO␣.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that GRO␣ can support monocyte arrest to the endothelium in models of inflammation and may thereby be relevant for the development of atherosclerosis (45). Moreover, enhanced plasma levels of GRO␣ in patients with coronary artery disease have been demonstrated (46). Although these measurements were based on GRO␣ expression in peripheral monocytes, it is tempting to speculate that activated endothelial cells could contribute significantly to the total expression and secretion of GRO␣.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Boos et al observed a significant increase in vWF and E-selectin after elective PCI [15], which may seem to be in conflict with the present study showing no change (vWF) or a decrease (E-selectin) in these markers after PCI. However, cardiovascular medications, and in particular statins, may influence the degree of endothelial cell activation and could contribute to differences in endothelial related PCI responses between different study populations [16]. Moreover, the endothelial related release of E-selectin seems to be differently regulated from that of VCAM-1 [17,18], and both the increase in VCAM-1 and the decrease in E-selectin may reflect some degree of endothelial dysfunction during PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Human PDL cells and gingival fibroblasts have previously been reported to respond to inflammation promoters by producing other cytokines like IL-6 and MCP-1 [10,11,19], suggesting that oral fibroblast contribute to the production of several important factors involved in inflammation. Breland et al [20] have reported data suggesting that GROa is involved in atherogenesis and atherosclerosis. It is possible that GROa, produced by oral fibroblasts, has a role not only in periodontitis but also in vascular inflammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%